Aquaporin–graphene interface: relevance to point-of-care device for renal cell carcinoma and desalination. Issue 3 (6th June 2018) - Jakowiecki, Jakub; Sztyler, Agnieszka; Filipek, Slawomir; Li, Pingzuo; Raman, Karthik; Barathiraja, Natarajan; Ramakrishna, Seeram; Eswara, Jairam R.; Altaee, Ali; Sharif, Adel O.; Ajayan, Pulickel M.; Renugopalakrishnan, Venkatesan
Abstract : The aquaporin superfamily of hydrophobic integral membrane proteins constitutes water channels essential to the movement of water across the cell membrane, maintaining homeostatic equilibrium. During the passage of water between the extracellular and intracellular sides of the cell, aquaporins act as ultra-sensitive filters. Owing to their hydrophobic nature, aquaporins self-assemble in phospholipids. If a proper choice of lipids is made then the aquaporin biomimetic membrane can be used in the design of an artificial kidney. In combination with graphene, the aquaporin biomimetic membrane finds practical application in desalination and water recycling using mostly Escherichia coli AqpZ. Recently, human aquaporin 1 has emerged as an important biomarker in renal cell carcinoma. At present, the ultra-sensitive sensing of renal cell carcinoma is cumbersome. Hence, we discuss the use of epitopes from monoclonal antibodies as a probe for a point-of-care device for sensing renal cell carcinoma. This device works by immobilizing the antibody on the surface of a single-layer graphene, that is, as a microfluidic device for sensing renal cell carcinoma.